An Applied Study: Investigate the relationship of cash flows, capital expenditure and the ratio of shares issued according to the price coefficient (Case Study: Companies accepted in Tehran Stock Exchange) - Hematfar, Mahmood (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
The interests of an investor in an enterprise include: Future earnings, future cash flows and paying future cash dividends, Investing in these interests is demanded by investors and awareness of both the profit and future cash flows draws more attention. The purpose of this study is to investigate the effect of cash flows, capital expenditures and stocks on the price coefficient. This research is an applied research in terms of purpose it also falls into the descriptive-correlational research group in terms of inferring research hypotheses, combined regression models and panel data were used to test the hypotheses, multivariate linear regression test (year-company) was used to test the hypotheses. It is a library and analytical-scientific study based on panel data analysis (panel data). After collecting the required information from the companies involved, the research hypotheses were analyzed using correlation and regression analysis and data analysis panel method, initially, preliminary calculations were performed in Excel software and the data was prepared for analysis, then 10 E views software was used to perform the final analysis. In this study, financial information of 101 companies listed in Tehran Stock Exchange during the period 1391 to 1396 (660 companies - year) was reviewed. Based on the analysis carried out to confirm the first hypothesis of the study, we concluded that: There is a significant and direct relationship between cash flows and capital expenditures of companies with respect to the price coefficient of each share. We also concluded that, in support of the second research hypothesis: There is a significant and direct relationship between the ratio of issued stocks and the accumulated cash flows of companies according to the price coefficient.